BIAYA OPERASIONAL KENDARAAN PADA DINAS PERUMAHAN RAKYAT KAWASAN PERMUKIMAN DAN DINAS PEKERJAAN UMUM PENATAAN RUANG PROVINSI ACEH - M. Aris Maulana; Renni Anggraini; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2018)
The employee transportation service is an application of traffic management using vanpooling. Vanpooling is an activity of using a vehicle together or sharing a car on the way so that more than one person is in the van in one travel route. Vanpooling is able to reduce the use of private vehicles to the center of the activity with a fleet of special transport employees. The potential for employee specific transport is enormous and 83% agree with the implementation of the traffic management. The employee specific operating freight operational systems are determinations with residential area corridors and passing major road routes at the address of each employee. In the operation of a transport both personal, general and special, not apart from the vehicles operating costs (VOC). Therefore, an analysis of the need for the development of special transportation of employees in the Dinas Perumahan Rakyat Kawasan Permukiman dan Dinas Pekerjaan Umum Penataan Ruang Province of Aceh. The method used in this study is descriptive - quantitative, by distributing questionnaires to obtain quantitative data in determining VOC. The results of the VOC of private and special vehicles are summarized in a descriptive conclusion. The result of the research shows that employee characteristics of the data are processed to determine vehicle operating cost of private vehicles as well as the special transport vehicles of employees. The overall VOC of private vehicles is Rp. 2.486.377.640, while the value VOC of employee specific transport vehicles is Rp. 685.043.840.